Story(telling) gender – Gender Stereotypes in Contemporary Portuguese Children's Literature - Nunes, A. (10th European Network of Picturebook Research Conference: Understanding the World: Multiculturality, Interculturality and Global Citizenship in Picturebooks, 2025)
Oral participation at the doctoral workshop which aimed to give early career researchers the opportunity to present and discuss their picturebook-related doctoral projects with renowned scholars working in the field of picturebook research. I presented my PhD research intitled: "Story(telling) gender – Gender Stereotypes in Contemporary Portuguese Children's Literature" and commented on other colleague's work.